Complementary Mechanisms Potentially Involved in the Pathology of Zika Virus - Ojha, Chet Raj; Rodriguez, Myosotys; Lapierre, Jessica; Muthu Karuppan, Mohan Kumar; Branscome, Heather; Kashanchi, Fatah; El-Hage, Nazira (Frontiers in Immunology, 2018)
Zika virus (ZIKV) has emerged as a global health threat due to its neuro-teratogenic effect and wide range of transmission routes. Most recently, ZIKV infection has been linked with both autoimmune disorders in adults and neurodevelopmental disorders in newborns. Researchers are exploring potential cellular and molecular mechanisms underlying the neuro-teratogenicity and related consequences by using various in vitro cell culture methods and in vivo animal models. Though some of the putative viral entry receptors have been identified for ZIKV entry into the target cells, the exact mechanism of ZIKV entry or induced pathology are still not clear. Some of the important host cellular pathways including the Toll-like receptor (TLR), autophagy, apoptosis and unfolded protein response (UPR) pathways are considered potential mechanism(s) for ZIKV induced neuroinflammation and for neurodevelopmental disorders. Since there is still a dire need for efficient treatment and vaccine to prevent ZIKV mediated disorders, a better understanding of the interaction between virus and host cellular pathways could pave the way for development of targeted therapeutic intervention. In this review, we are focusing on the recent advances and current knowledge regarding the interaction of ZIKV with abovementioned pathways so as to provide basic understanding to execute further research that could aid in the development of novel therapeutic strategy.